3D-printed nerve conduit with vascular networks to promote peripheral nerve regeneration. (December 2019) - Tao, Jie; He, Yan; Wang, Shuai; Mao, Jian
Abstract: Peripheral nerve regeneration remains a challenge in tissue engineering and regenerative medicine. However, the existing approaches have limited regenerative capability. 3D-printed nerve conduits with well-defined properties are potent tools to facilitate peripheral nerve regeneration after injuries. Meanwhile, the vascular networks within the constructs can promote the exchange of oxygen, neurotrophic factors, and removal of waste products, thereby providing an advantageous microenvironment for tissue regeneration. It will be an interesting approach to integrate 3D-printed nerve conduit with vascular networks for the guidance of regenerated nerves. We hypothesize that 3D-printed vascularized nerve conduit will be an effective platform to promote nerve regeneration and functional restoration.